(NoPYT ANALIZA TWOR^ESTWA (B. (Np(B. (Ni(B. (N~AJKOWSKOGO(B.(1864-1878)s (NmONOGRAFIQs - (Na(B. (NaLX[WANGs ((NlENINGRAD(B.s (NmUZYKAs, 1950)
(N~AJKOWSKOGO NEREDKO I SOWER[ENNNO OSNOWATELXNOGO NAZYWA@T WELI^AJ[IM SIMFONISTOM(B.s
Keywords: (NFORTEPIANOs